(untitled) (Journal of Engineering, 2018)
The constructed building in the urban area is subject to wind characteristics due to the influence of surrounding buildings. The residential complexes currently being built in Iraq represent a case study for the subject of this research. Therefore, the objective of this study is to identify the interference effect because of adjacent buildings effects on the mid-rise building. The speed and pressure of the wind have been numerically simulated as well as wind load has been simulated by using a virtual wind tunnel which is available in Autodesk Robot Structural Analysis, RSA, software. Two identical adjacent buildings have been simulated and many coefficients were included in this study such as the spacing, directionality, and elevation of adjacent building coefficients. The results of the study showed that the neighboring building could increase or decrease the wind pressure significantly so that it cannot be neglected.